'Murderous energy' in Oaxaca, Mexico: wind factories, territorial struggle and social warfare. Issue 2 (23rd February 2022) - Dunlap, Alexander; Arce, Martín Correa
ABSTRACT: This article examines the struggle against the new Électricité de France (EDF) wind park, Gunaa Sicarú, in Unión Hidalgo (UH), Mexico. Foregrounding Indigenous land defense, the article refers to wind energy as 'wind factories' to discuss agrarian change in the region. Revealing the counterinsurgency colonial model as a foundational approach to extractive development, the article argues that the distribution of money, Sicarios (hitmen) and non-governmental organizations (NGOs) are instrumental to engineering 'social acceptance'. Moreover, the liberalism underlining NGOs, if not careful, advances processes of infrastructural colonization and, consequently, wider trajectories of (neo)colonialism.